Percepción de la utilidad del referente teórico para la aplicación práctica del ejercicio profesional de graduados en contabilidad y auditoría. - Muñoz Martinez, Vinicio Manfreddy (My University, 2019)
The purpose of this research project is to investigate the current reality of the accounting processes applied in companies, that is, to identify through the graduates in accounting and auditing the perception of the usefulness of the theoretical reference to apply it in the practice of professional practice. The importance of generating progress in the processes motivates professionals to research to learn and execute knowledge of the new accounting changes in the business market, accounting research is not to collect information from other scientific studies but to acquire that information and feed knowledge of the new systematic advances. The proposal poses a problem. Is there no scientific research in the accounting processes of market companies for the improvement of accounting in the professional practice?. Indicates the importance of developing the topic and justifies its execution. For the study we worked with the research methodology through the survey technique to a universe of 2500 accountants of the El Oro Province of the Accountants School of El Oro with a sample of 345 surveys. A general objective was established to evaluate the level of perception of the usefulness of the theoretical reference for the practical application of the professional practice of the graduates in accounting and auditing. By means of the development a referential theoretical framework of the topics related to the theoretical reference for the professional practice is made, we find the analysis the results of the questions posed to the graduates and generates important conclusions of the investigated topic.
El presente proyecto investigativo tiene como propósito investigar la realidad actual de los procesos contables aplicados en las empresas, es decir identificar a través de los graduados en contabilidad y auditoría la percepción de la utilidad del referente teórico para aplicarlo en la práctica del ejercicio profesional. La importancia de generar avances en los procesos motiva a los profesionales investigar para aprender y ejecutar conocimientos de los nuevos cambios contables en el mercado empresarial, la investigación contable no es recoger la información de otros estudios científicos sino de adquirir esa información y alimentar conocimiento de los nuevos avances sistemáticos. La propuesta plantea una problemática ¿No existe investigación científica en los procesos contables de las empresas del mercado para el mejoramiento de la contabilidad en el ejercicio profesional? Indica la importancia de desarrollar el tema y justifica su ejecución. Para el estudio se trabajó con la metodología de investigación mediante la técnica de encuesta a un universo de 2500 contadores de la Provincia de El Oro del Colegio de Contadores de El Oro con una muestra de 345 encuestas. Se estableció un objetivo general para evaluar el nivel de percepción de la utilidad del referente teórico para la aplicación práctica del ejercicio profesional de los graduados en contabilidad y auditoría. Mediante el desarrollo se hace un marco teórico referencial de los temas relacionados al referente teórico para la práctica profesional, encontramos el análisis los resultados de las preguntas planteadas a los graduados y se genera conclusiones importantes del tema investigado.
Keywords: CONTABILIDAD; INVESTIGACIÓN CONTABLE; PRODUCCIÓN CIENTÍFICA; EDUCACIÓN CONTABLE; COMPETENCIAS